Leadership Styles and Employees’ Job Satisfaction: A Case from the Private Banking Sector of Pakistan - Javed, Hafiz Ali; Jaffari, Asad Abbas; Rahim, Muzahir (Journal of Asian Business Strategy, 2014)
This research study shows the relationship of leadership styles with the job satisfaction of employees working in the private banking sector of Pakistan and also depicts which leadership style leaders have adopted most. A questionnaire with five points likert scale was used to collect data on different dimensions of leadership styles and employees’ job satisfaction from 230 participants working in five selected private banks of four districts of the province of Punjab, Pakistan. The results showed that there is a significant relationship between transactional leadership style and employees’ job satisfaction and this transactional leadership style is more adopted by the leaders as compared to transformational leadership style. The research results are very important for the higher management of targeted banks in terms of to increase employees’ job satisfaction they can train their leading staff in branches to adopt transactional leadership style. This research article comes to an end with a brief conclusion, limitations and recommendations.